Mechanical analysis of pinning points in the Ross Ice Shelf, Antarctica - Holly Still; Adam Campbell; Christina Hulbe (Annals of Glaciology, 2019)
Ice shelves regulate the rate of ice-sheet discharge along much of the Antarctic coastline. Pinning points, sites of localised grounding within floating ice, can in turn, regulate the flow and thickness of an ice shelf. While the net resistive effect of ice shelves has been quantified in a systematic way, few extant pinning points have been examined in detail. Here, complete force budgets are calculated and examined for ice rises and rumples in the Ross Ice Shelf, West Antarctica. The diverse features have different effects on ice shelf mechanics that do not depend simply on their size but may, we conclude, depend on the properties of seafloor materials.